Transformation Of Family Law In Algeria Analysis Of The Pre- And Post Independence Period - Andri Gustamar; Efrinaldi Efrinaldi; Rahmat Hidayat; Benazza Amal (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
This study aims to reveal the influence of family law reform in Algeria on the socio-cultural life patterns of its people. As one of the Muslim countries in the African continent, Algeria has gone through various stages of legal reform, especially in the field of family law. These efforts include modernizing regulations, increasing the protection of women's rights, and adapting to changing social and cultural developments. Cultural and social values ​​play an important role in the formation of family law in this country. The findings of the study show that during the Ottoman Turkish rule, Islam was the main foundation in regulating people's lives. However, the arrival of French colonialism had a significant impact on the resilience of the Islamic legal system, as seen from France's efforts to integrate elements of European law into the existing Islamic legal system. On the other hand, French colonization also encouraged the development of family law in Algeria, as reflected in the ratification of the Marriage Law in 1959 known as the Ordinance. After gaining independence, Algeria experienced a major overhaul in its family law with the ratification of the Family Code 1984, which was later amended through Ordinance No. 2 of 2005.